Improved Tracking and Resolution of Bacteria in Holographic Microscopy Using Dye and Fluorescent Protein Labeling - Nadeau, Jay L.; Cho, Yong Bin; Kühn, Jonas; Liewer, Kurt (Frontiers in Chemistry, 2016)
Digital holographic microscopy (DHM) is an emerging imaging technique that permits instantaneous capture of a relatively large sample volume. However, large volumes usually come at the expense of lower spatial resolution, and the technique has rarely been used with prokaryotic cells due to their small size and low contrast. In this paper we demonstrate the use of a Mach-Zehnder dual-beam instrument for imaging of labeled and unlabeled bacteria and microalgae. Spatial resolution of 0.3 micrometers is achieved, providing a sampling of several pixels across a typical prokaryotic cell. Both cellular motility and morphology are readily recorded. The use of dyes provides both amplitude and phase contrast improvement and is of use to identify cells in dense samples.